2013
DOI: 10.1111/nhs.12095
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the predictive validity of an emergency department mental health triage tool

Abstract: Emergency department mental health triage is a complex clinical task for which the evidence base is minimal.Research in the past decade has consistently identified issues associated with the accuracy and consistency of mental health triage assessment. In this study, we investigated the predictive validity of the clinical descriptors in the Victorian Emergency Department Mental Health Triage Tool. Using a naturalistic, retrospective study design, an audit of the emergency department triage database was undertak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 29 publications
(47 reference statements)
1
9
0
1
Order By: Relevance
“…An environment and a process that does not enable sound decision-making processes may have deleterious outcomes for the person such as incorrect triage scores and clinically inappropriate waiting times Hinson et al (2019). Retrospective studies indicate that triage nurses can accurately identify urgency using a specialised mental health triage scale (Sands et al, 2014) but this study provides insight into the challenges ED triage nurses face in order to assess people with mental illness. It is posited that more attention to environmental design that facilitates privacy and less disruption, and specific education regarding mental health acuity would improve ED triage assessment and facilitate more meaningful engagement with, and assessment of, people presenting with a mental illness.…”
Section: Responsementioning
confidence: 91%
See 1 more Smart Citation
“…An environment and a process that does not enable sound decision-making processes may have deleterious outcomes for the person such as incorrect triage scores and clinically inappropriate waiting times Hinson et al (2019). Retrospective studies indicate that triage nurses can accurately identify urgency using a specialised mental health triage scale (Sands et al, 2014) but this study provides insight into the challenges ED triage nurses face in order to assess people with mental illness. It is posited that more attention to environmental design that facilitates privacy and less disruption, and specific education regarding mental health acuity would improve ED triage assessment and facilitate more meaningful engagement with, and assessment of, people presenting with a mental illness.…”
Section: Responsementioning
confidence: 91%
“…However, unlike the ED triage of people with physical injury and illness, for whom there is one standardised triage scale, there is no consistent approach to triaging people with mental illness . Despite this, research has shown that it is possible to accurately identify signs and symptoms of mental illness (Sands et al, 2014). The difficulty posed by the busy and acute ED environment and mental health knowledge deficits, are recognised as influencing the triage process.…”
Section: Responsementioning
confidence: 99%
“…There is no standard system for assessing the validity of triage systems. For evaluation of the validity of AMHTS in many studies, parameters such as waiting time in triage, length of stay in the emergency room, nurses' ability to identify acute psychosis symptoms and evaluate treatment acuity in triage, and time to discharge were used (Smart et al, 1999; Sands, et al, 2014). In the study, the difference between nurses' ability to determine treatment acuity, patient waiting time according to triage category, patient waiting time, and patient satisfaction data obtained before and during the AMHTS application were analyzed statistically.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, The Australian Mental Health Triage Scale (AMHTS) developed and used as a guide by Broadbent et al (2002 ), Smart et al (1999 ), proven to reliable among referees (Broadbent et al, 2020; Mental Health Triage, Health Policy Priorities Principal Committee, 2011) and has high sensitivity in the evaluation of patients with mental problems (Broadbent et al, 2020; Downey et al, 2015a). The main goal of the AMHTS is not to increase or decrease patient waiting times, but to determine the waiting times of priority patients and to make the waiting times of these patients more appropriate to their needs (Sands et al, 2014). It helps nurses (and other professionals) to understand the patient's condition better and to link the patient to appropriate treatment sooner so that the patient recovers faster (Broadbent et al, 2020; Smart et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In the early 1990s, Australia implemented the National Triage Scale, which was later renamed Australasian Triage Scale (ATS) (Pardey, ; FitzGerald et al ., ). This system is reportedly the most commonly‐used triage system in the world (Qureshi, ; Sands et al ., ). The ATS is a five‐tier scale that has formed the basis for other triage scales, such as the Canadian Emergency Department Triage and Acuity Scale, Manchester Triage Scale, and systems in other countries, such as Hong Kong, New Zealand, and Belgium (Pardey, ; Christ et al ., ; Fitzgerald et al ., ).…”
Section: Introductionmentioning
confidence: 97%